2015
DOI: 10.1103/physrevb.91.085109
|View full text |Cite
|
Sign up to set email alerts
|

Resolving unoccupied electronic states with laser ARPES in bismuth-based cuprate superconductors

Abstract: Angle-resolved photoemission spectroscopy (ARPES) is typically used to study only the occupied electronic band structure of a material. Here we use laser-based ARPES to observe a feature in bismuth-based superconductors that, in contrast, is related to the unoccupied states. Specifically, we observe a dispersive suppression of intensity cutting across the valence band, which, when compared with relativistic one-step calculations, can be traced to two final-state gaps in the bands 6 eV above the Fermi level. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…Numerical techniques such as division by the Fermi-Dirac distribution have been used to reveal the states slightly above E F [10], yet this method is confined to an energy range on the order of the sample temperature. A recent ARPES study on Bi-based cuprates identified features contributed by unbound states at 6 eV above E F [11]. However, the key quantities of the strong correlation physics in cuprates -the energy scale of the UHB and the Coulomb interaction strength -remain underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical techniques such as division by the Fermi-Dirac distribution have been used to reveal the states slightly above E F [10], yet this method is confined to an energy range on the order of the sample temperature. A recent ARPES study on Bi-based cuprates identified features contributed by unbound states at 6 eV above E F [11]. However, the key quantities of the strong correlation physics in cuprates -the energy scale of the UHB and the Coulomb interaction strength -remain underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting dispersions cannot be well described as two distinct bands, as the bands "twist" around each other (as guided by the red dashed curves), and seem to "switch momenta" at certain binding energies (as indicated by the yellow arrows), which change roughly by the same amount as the difference in photon energy. This behavior suggests that the spectrum is modulated by the structure of final states 32 , and therefore cannot be understood solely in the context of a well-defined initial state dispersion. More detailed calculations involving electron final-states are required to fully understand this complexity 33 .…”
mentioning
confidence: 99%
“…Accessing spin-textures of the TSSs via spin-resolved ARPES (SARPES), on the other hand, has generally proven to be more challenging. For example, circular-dichroism ARPES (CD-ARPES) experiments, where one measures the difference in ARPES intensities for right-and left-circularly polarized light, show that the CD-ARPES spectrum changes sign with photon energy from the same sample of a Bi 2 Te 3 single crystal, making it clear that CD-ARPES cannot provide a probe of the initial state spin structure [15][16][17] . These results are not surprising since it is well-known that spectral intensities in highly resolved spectroscopies such as ARPES depend sensitively on matrix element effects, which in the case of ARPES involve not only the properties of the initial state but also of the final state wave functions [18][19][20] .…”
Section: Topological Insulators (Tis)mentioning
confidence: 99%
“…As in our previous laser ARPES studies, we chose a small value of the imaginary part, Σ f " = 0.1 eV (full-width-at-halfmaximum of 0.2 eV), for the final state self-energy 16,17,24 . This value of Σ f " is comparable to the value of 0.2 eV for low photon energies suggested by Strocov et al 25 .…”
Section: Computationsmentioning
confidence: 99%
See 1 more Smart Citation